Ser extranjero (Signo de los tiempos e interpelación de la fe) - Dussel, Enrique D. (Bollettino Filosofico, 2019)
The essay starts by referring to the new concept of “enemy” and “foreign” which comes up from the New Testament. On one hand, it shows the interweaving between “foreign” and “power” and, on the other, the metaphysical and theological dimension of otherness for which God reveals himself in the system through those who don’t belong to the system. However, the analysis in not only religious and metaphysical but also a political, social and economic analysis and it deals with Mexican migration to USA, in particular with braceros and mojados. The paper indicates four levels in the experience of being foreign which are related to the land (“left behind land”, “others’ land”, “liberation project land” and “eschatological land”) and different ways of being foreign, like “dominator”, “emigrant”, and “expatriate”. A very important role takes Grace conceived like praxis position in the reception of liberation. Keywords: Foreign, Poor, New Testament, Grace, Liberation